A study on order cycle process at Tamadam Bonded Warehouse / Hasmi Mokhlas - Mokhlas, Hasmi (1996)
This thesis discusses the order cycle process at Tamadam Bonded Warehouse. The purpose of this study is to examine the daily operation or order cycle process at TBW. Interviewing of forwarding agents and observation had been carried out to collect all data and information for this study. It was found that there were delays in the process of inbound and outbound of goods. But the problem is not very serious and could be acceptable from the view point of forwarding agents and consignees.